Bamboo: Global Occurrence and Its Significance as Food and Related Products - Utsaphong Uprarawanna; Jiraphat Kaewsritong; Khongsak Srikaeo (Crops)
Bamboo has recently garnered international recognition for its nutritional and medicinal properties, which contribute significantly to the culinary, pharmaceutical, and cosmeceutical sectors. Every component of the bamboo plant—rhizome, culm, bark shavings, shoots, leaves, roots, and seeds—possesses useful applications. Bamboo shoots, as a type of food, have been consumed for a long time due to their nutritional and edible qualities, as well as their economic value. Other parts of bamboo, such as leaves and culms, can also be used in food applications. Commercial markets in various countries offer a variety of bamboo-based products, including those that are dried, fermented, pickled, and thermally processed. This article provides an overview of the use of all edible bamboo parts as foods and related products as well as their nutritional benefits. A wide range of traditional food products derived from bamboo, including industrial products and some novel products, was investigated. It is possible that the promotion of bamboo as a staple food could offer substantial promise in addressing the worldwide concerns regarding hunger, food insecurity, and environmental degradation.